Materials for Well Integrity: Performance of Setting Materials for Well Cementing Operation - Kamali, Mohammadreza (Stavanger, University of Stavanger, 2022)
Primary cementing operation is the process of pumping and placing a cementitious slurry in a well. After setting, the so-called barrier material has to provide zonal isolation in the annular gap behind casing string. After a hundred years of using hydraulic Portland cement as prime material for cementing operation, although the chemistry of the material is well-developed, still shortcomings are reported in short- and long-term properties. Safe and cost-efficient operations have been the motivation for improving the performance of barrier material. Additionally, annual increase of the carbon tax is a driving force for switching to green alternatives to Portland cement. The present study includes scientific examination of candidate barrier materials for cementing operation. These materials are an industrial class of expansive cement, a non-cement-based pozzolanic material, an inorganic polymer known as geopolymer, and organic thermosetting resin. The materials were assessed aiming to evaluate their performance at equal conditions. The thesis is divided into two main sections comprising a core that describe the research project and appended papers discussing scientific achievements. The outcome of this study includes strengths and weaknesses of each material, which are published in seven scientific papers: three journals, two peer-reviewed conferences, and two SPE conferences. The papers are included as Appendix and labeled using Roman numerals. In the present review, same numerals are used when referring to the papers. Paper I includes fluid-state properties of the candidate barrier material. Density, viscosity profile, static fluid-loss, and the pumpability of the materials are tested at bottom-hole circulating temperature. Paper II presents short-term mechanical properties of Portland cement-based systems and highlights the effect of chemical additives on the mix design. In this study, the mechanical properties of expansive cement and API neat class G cement are included. The samples were cured from one day to ...